Learning Mechanisms Explaining Learning With Digital Tools in Educational Settings: a Cognitive Process Framework - Reinhold, Frank; Leuders, Timo; Loibl, Katharina; Nückles, Matthias; Beege, Maik; Boelmann, Jan M. (Educational psychology review, 2024)
To explain successful subject matter learning with digital tools, the specification of mediating cognitive processes is crucial for any empirical investigation. We introduce a cognitive process framework for the mechanisms of learning with digital tools (CoDiL) that combines core ideas from the psychology of instruction (utilization-of-learning-opportunity framework), cognitive psychology (knowledge-learning-instruction framework), and domain-specific research on learning and instruction. This synthesizing framework can be used to theoretically ground, firstly, the design of digital tools for learning, and secondly, the empirical analysis of students’ learning activities in digitally enriched educational settings via the analysis of specific student-tool interactions.